Pediatric dermatoses encountered in dermatology outpatient department of a teaching institute - Patel, Krina B.; Desai, Bhanu R. (International Journal of Contemporary Pediatrics, 2016)
Background:A child presenting with a skin problem is a common encounter in dermatology outpatient department. Various infectious and non-infectious disorders may be seen in children of all ages. Their severity may also vary from mild to severe but their presentation and management may be different from their adult counterpart. Aim of present study was to evaluate the spectrum of skin diseases in pediatric population of dermatology department of a teaching institute. Methods: A prospective study was undertaken to determine the pattern of skin diseases at the dermatology OPD of tertiary care hospital from January 2014 to December 2015. 3560 pediatric patients up to age of 14 years were included in the study. A detailed general, cutaneous and systemic examination of all patients was done along with necessary investigations as and when needed. The findings were recorded and data was analyzed. Results:Out of 3560 study group population there were 57.35% male and rest female. The highest numbers of patients were in the age group of > 10 to 14 years (41.04%) Majority of patients presented with infections and infestations (52.6%) Scabies was the most common disease found in patients. Many rare genodermatosis were observed in present study. Conclusions:Both preschool and school going children were found to be affected with skin diseases frequently. Infections were more commonly seen which reflect need for proper counselling of parents regarding maintenance of hygiene and skin care. Being a referral centre and tertiary care hospital, some of the rarest dermatoses were also found during present study.